(untitled) (Carte Romanze, 2023)
This paper proposes the study and critical edition of the crown of cantari on the Assumption of the Virgin transmitted from ms. 2273 of Biblioteca Angelica in Rome. The text, actually published only partially in anthology, is here transcribed and published in a conservative manner, with a commentary in wich we trace the main sources, for example some loci of Legenda aurea, biblical texts, hagiographies about Assumption (especially Transitus A and Transitus B by Pseudo-Melitone).